Utilization of Roots of Muli Banana Plants (Musa acuminata Linn.) as Antibiotics and Antiseptics - Nainggolan, Ribka Debora; Handayani, Kusuma; Mayuri, Nindya Sekar; Rumidatul, Alfi (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2025)
Diseases caused by bacteria can usually be combated by administering antibiotics and using antiseptics. However, there are some groups of pathogens, such Escherichia coli as well as Staphylococcus aureus, which are highly resistant to the antibiotics amoxicillin, penicillin, tetracycline and chloramphenicol. One of the efforts to control these bacteria is by using bioactive compounds derived from plants. Banana plants contain secondary metabolite compounds flavonoids, saponins, and tannins that can act as anti-infective agents, including muli banana (Musa acuminata Linn.). Banana plant roots as natural ingredients can be an alternative to antiseptics because they contain antibacterial compounds with milder side effects than long-term use of alcohol-based antiseptics that can reduce skin moisture. This study was conducted to determine the efficacy of banana muli root extract (M. acuminata Linn.) as an antibiotic and antiseptic. The hypothesis in this study is that the root extract at a certain concentration is thought to have effectiveness as an antibiotic (E. coli) and antiseptic (S. aureus). In this study, the Kirby-Bauer method was applied by agar diffusion and the results of the inhibition zone test were formed around the paper disc. The results showed that the optimum efficacy of muli banana root extract (M. acuminata Linn.) as an antibiotic (E. coli ATCC 25922) was at a concentration of 95% (2.96 mm) and as an antiseptic (S. aureus ATCC 25923) at a concentration of 75% (9.1 mm).